[(18)F]FDG Uptake in the Aortic Wall Smooth Muscle of Atherosclerotic Plaques in the Simian Atherosclerosis Model - Iwaki, Takayuki (Biomed Res Int, 2016)
Atherosclerosis is a self-sustaining inflammatory fibroproliferative disease that progresses in discrete stages and involves a number of cell types and effector molecules. Recently, [(18)F]fluoro-2-deoxy-D-glucose- ([(18)F]FDG-) positron emission tomography (PET) has been suggested as a tool to evaluate atherosclerotic plaques by detecting accumulated macrophages associated with inflammation progress. However, at the cellular level, it remains unknown whether only macrophages exhibit high uptake of [(18)F]FDG. To identify the cellular origin of [(18)F]FDG uptake in atherosclerotic plaques, we developed a simian atherosclerosis model and performed PET and ex vivo macro- and micro-autoradiography (ARG). Increased [(18)F]FDG uptake in the aortic wall was observed in high-cholesterol diet-treated monkeys and WHHL rabbits. Macro-ARG of [(18)F]FDG in aortic sections showed that [(18)F]FDG was accumulated in the media and intima in the simian model as similar to that in WHHL rabbits. Combined analysis of micro-ARG with immunohistochemistry in the simian atherosclerosis model revealed that most cellular [(18)F]FDG uptake observed in the media was derived not only from the infiltrated macrophages in atherosclerotic plaques but also from the smooth muscle cells (SMCs) of the aortic wall in atherosclerotic lesions.